Natural Product Chemistry for Drug Discovery - Antony D Buss [ editor ] (Royal Society of Chemistry, 2010)
Natural Product Chemistry for Drug Discovery provides a comprehensive summary of where natural product chemistry is today in drug discovery. The book covers emerging technologies and case studies and is a source of up-to-date information on the topical subject of natural products. Natural products are once again considered important tools in the drug discovery toolbox. The authors are all experts in their respective fields of natural product chemistry.